PARA ALÉM DO LIVRO E DA SALA DE AULA: A CONTROVÉRSIA DOS AGROTÓXICOS NA PRÁXIS DA PEDAGOGIA DA ALTERNÂNCIA (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This work aims to present experiences and thoughts based on an etnographic research with educators and students from an Agricultural Family School (EFA, in Brazil) in the State of Espírito Santo (ES), whose pedagogical work is guided by Pedagogy of Alternation. The accompaniment of a group of 14 students of the 4th year of the Technical Course in Agriculture, in a dynamic between School-Time and Community-Time, in the elaboration and realization of a Study Plan with the thematic of olericulture (conventional and organic) allowed us to observe crossings that immersion with the local reality makes possible in the training of EFA agricultural technicians, favoring the critical and engaged training of future professionals. The debate on the pesticides use and the production of knowledge as a basis for decision-making are amplified by incorporation of farmers knowledge, immersed in the cultural, economic and social issues of the local reality.
Keywords: Socio-Scientific Controversie; Dialogicity; Pesticides; Alternation; Agricultural Family School